Effects of a Single Proprioceptive Neuromuscular Facilitation Stretching Exercise With and Without Post-stretching Activation on the Muscle Function and Mechanical Properties of the Plantar Flexor Muscles - Reiner, Marina; Tilp, Markus; Guilhem, Gaël; Morales-Artacho, Antonio; Nakamura, Masatoshi; Konrad, Andreas (Frontiers in Physiology, 2021)
A single proprioceptive neuromuscular facilitation (PNF) stretching exercise can increase the range of motion (ROM) of a joint but can lead to a decrease in performance immediately after the stretching exercise. Post-stretching activation (PSA) exercises are known as a possible way to counteract such a drop in performance following a single stretching exercise. However, to date, no study has investigated the combination of PNF stretching with PSA. Thus, the aim of this study was to compare the effects of a PNF stretching exercise with and without PSA on the muscle function (e.g., ROM) and mechanical properties of the plantar flexor muscles. Eighteen physically active males volunteered in the study, which had a crossover design and a random order. The passive shear modulus of the gastrocnemius medialis (GM) and gastrocnemius lateralis (GL) was measured in a neutral position with shear wave elastography, both pre- and post-intervention. Maximum voluntary isometric contraction (MVIC) peak torque, maximum voluntary dynamic contraction peak torque, dorsiflexion ROM, and passive resistive torque (PRT) were also measured with a dynamometer. The interventions were 4×30s of PNF stretching (5s of contraction) and two sets of three exercises with 20 or 40 fast ground contacts (PNF stretching+PSA) and PNF stretching only. ROM was found to have increased in both groups (+4%). In addition, the PNF stretching+PSA group showed a decrease in PRT at a given angle (−7%) and a decrease in GM and mean shear modulus (GM+GL; −6%). Moreover, the MVIC peak torque decreased (−4%) only in the PNF stretching group (without PSA). Therefore, we conclude that, if PNF stretching is used as a warm-up exercise, target-muscle-specific PSA should follow to keep the performance output at the same level while maintaining the benefit of a greater ROM.